Children and television a global perspective - Lemish, Dafna 1951- (Malden, MA Blackwell Pub, 2007)
This book offers a magisterial overview on children and television from the accumulated global literature in this field of the past 50 years, combinig both the American tradition, influenced heavily by developmental psychological studies, as well as European tradition, characterized by more sociological and cultural studies perspectives to the field
The home of television viewing -- Television and individual development -- Television and the behavior of children -- Television and the social construction of reality -- Television and learning -- Implications for education and policy -- Conclusion: growing up in a global screen culture
Includes bibliographical references (p. [222]-245) and index
3
Keywords: Television and children; Television broadcasting -- Social aspects; Television in education